DECONSTRUCTING THE MAIN CHARACTERS IN KHALED HOSSEINI’S THE KITE RUNNER NOVEL - Azizah, Nurul; Kuncara, Singgih Daru; Valiantien, Nita Maya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
This paper discussed the deconstruction of the fixed meaning of the main characters in Khaled Hosseini’s The Kite Runner novel named Amir and Hassan. The purposes of this thesis are to determine how the fixed meaning of Amir and Hassan’s characters is described in the novel and to comprehend how Derrida’s deconstruction theory may help us to find a new meaning of Amir and Hassan’s characters. The research used a descriptive qualitative method and deconstruction approach. Further, the theories that are used in this analysis are the theories of deconstruction from Jacques Derrida and Boggs and Petrie’s theory of characterization. The results of this thesis showed that there are three characteristics of each character that has the opposite meaning. Firstly, Amir’s character was described as someone who has the character of selfish, superior, and coward. But after analyzing deeply, Amir’s character also has the opposite side of his characters, they are: selfless, inferior, and also brave character. Meanwhile, Hassan was described as an uneducated, brave, and good character, but he also has the opposite character. The new meaning of Hassan was described as educated, coward, and bad character.